Integration of metabolic and transcriptomic analyses for revealing the galactose metabolism of tobacco (Nicotiana tabacum) under salt stress - Bai, Ge; Zhang, Hui; Li, Yong; Yang, Da-Hai; Fei, Mingliang; Pang, Tao; Fu, Yaning; Yang, Ai-Guo; Wang, Zhen-Yu; Gu, Jinbao; Xie, He (Frontiers in Plant Science, 2025)
BackgroundSoil salinization poses a global threat to agriculture, necessitating strategies to enhance plant salt stress tolerance. Understanding the metabolic and transcriptomic responses of tobacco plants to salt stress is crucial for developing such strategies.ResultsThis study identified 238 up-regulated and 122 down-regulated metabolites in tobacco plants under long-term salt stress. Initial stress stages activated galactose and sucrose metabolic pathways. Chlorophyll synthesis was impacted by decreased 5-aminolevulinic acid production, while proline accumulation helped mitigate cell damage. Metabolite-metabolite correlation analysis revealed significant correlations among metabolites, and enrichment analysis highlighted benzamides, amino acids, fatty acids, and monosaccharides. Transcriptome analysis identified 8,386 differentially expressed genes, with enriched pathways in hormone signaling, photosynthesis, and amino acid metabolism. Integrated analysis confirmed the involvement of sucrose pathway in the salt response, validated by qRT-PCR.ConclusionsThis study provides a comprehensive understanding of the regulatory networks in tobacco during salt stress. The findings lay the groundwork for future research on plant stress responses and the development of salt-tolerant tobacco cultivars.